2004
DOI: 10.1523/jneurosci.2476-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Switching of NMDA Receptor 2A and 2B Subunits at Thalamic and Cortical Synapses during Early Postnatal Development

Abstract: Switching of the NMDA receptor 2A (NR2A) and NR2B subunits at NMDA receptors is thought to underlie the functional changes that occur in NMDA receptor properties during the developmental epoch when neural plasticity is most pronounced. The cellular expression of NR2A and NR2B and the NR2 synaptic binding protein postsynaptic density-95 (PSD-95) was examined in the mouse somatosensory cortex and thalamus from postnatal day 2 (P2) to P15 using reverse transcription-PCR, in situ hybridization histochemistry, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
238
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(260 citation statements)
references
References 52 publications
20
238
0
2
Order By: Relevance
“…Here we show definitive ultrastructural evidence of this switch in hippocampal synapses. This appears to be the common pattern in the central nervous system (Erisir and Harris, 2003;Liu et al, 2004) although there are exceptions, such as for some motoneurons that express abundant NR2A early in development (Oshima et al, 2002). In Sans et al (2000), we also showed the switch in the MAGUK composition of hippocampus using both immunoblots and immunogold localization at synapses (i.e., SAP102 decreases and PSD-95 and PSD-93 increase).…”
Section: Discussionsupporting
confidence: 52%
“…Here we show definitive ultrastructural evidence of this switch in hippocampal synapses. This appears to be the common pattern in the central nervous system (Erisir and Harris, 2003;Liu et al, 2004) although there are exceptions, such as for some motoneurons that express abundant NR2A early in development (Oshima et al, 2002). In Sans et al (2000), we also showed the switch in the MAGUK composition of hippocampus using both immunoblots and immunogold localization at synapses (i.e., SAP102 decreases and PSD-95 and PSD-93 increase).…”
Section: Discussionsupporting
confidence: 52%
“…These late EPSCs are selectively suppressed by increasing the viscosity of the extracellular space, a manipulation known to retard extrasynaptic transmission (Min et al, 1998;Perrais and Ropert, 2000;Nielsen et al, 2004). They also depend on NR2B-containing NMDA receptors, a population thought to be mainly extrasynaptic in the adolescent and adult rat (Stocca and Vicini, 1998;Rumbaugh and Vicini, 1999;Tovar and Westbrook, 1999;Townsend et al, 2003;Liu et al, 2004). However, the late EPSCs cannot be mimicked simply by increased ambient glutamate after uptake is blocked with TBOA.…”
Section: Discussionmentioning
confidence: 99%
“…The convergence of their effects helps to rule out the likelihood that their suppression of DOI-elicited late EPSCs was nonspecific. While NR2B receptors are omnipresent in the young rat, by adulthood they are thought to be located mainly at extrasynaptic locations (Stocca and Vicini, 1998;Rumbaugh and Vicini, 1999;Tovar and Westbrook, 1999;Townsend et al, 2003;Liu et al, 2004; but see Charton et al, 1999). Ultrastructural studies show them postsynaptically at the edge of synapses .…”
Section: Possible Recruitment Of Presynaptic Nmda Receptorsmentioning
confidence: 99%
“…Finally, two interesting things we can mention further about NR2B are:1) NR2B is more important than NR2A during brain development, and although this reverses as the brain matures, authors make important statements that NR2B subunits still abound in the mature brain 88,89 ; and 2) LeDoux's model is concerned with NR2B because it is critical in the acquisition of fear conditioning, and they have found a selective blocker of NR2B receptors, ifenprodil, to be effective in blocking acquisition. 73 …”
Section: Nmda Receptor Subunits In Ltp and Ltdmentioning
confidence: 99%